Shock Breakouts from Compact Circumstellar Medium Surrounding Core-collapse Supernova Progenitors May Contribute Significantly to the Observed ≳10 TeV Neutrino Background - Eli Waxman; Tal Wasserman; Eran O. Ofek; Avishay Gal-Yam (The Astrophysical Journal)
Growing observational evidence suggests that enhanced mass loss from the progenitors of core-collapse supernovae (SNe) is common during  ~1 yr preceding the explosion, creating an optically thick circumstellar medium (CSM) shell at  ~10 ^14.5 cm radii. We show that if such mass loss is indeed common, then the breakout of the SN shock through the dense CSM shell produces a neutrino flux that may account for a significant fraction of the observed  ≳10 TeV neutrino background. The neutrinos are created within a few days from the explosion, during and shortly after the shock breakout, which produces also large UV (and later X-ray) luminosity. The compact size and large UV luminosity imply a pair production optical depth of  ~10 ^4 for  > 100 GeV photons, naturally accounting for the lack of a high-energy gamma-ray background accompanying the neutrino background. SNe producing  >1 neutrino event in a 1 km ^2 detector are expected at a rate of  ≲0.1 yr ^−1 . A quantitative theory describing the evolution of the electromagnetic spectrum during a breakout, as the radiation-mediated shock is transformed into a collisionless one, is required to enable (i) using data from upcoming surveys that will systematically detect large numbers of young,  <1 day old SNe to determine the preexplosion mass-loss history of the SN progenitor population, and (ii) a quantitative determination of the neutrino luminosity and spectrum.